(untitled) (Current Problems in Rail Vehicles, 2021)
From a social point of view, there is a growing demand to increase traffic safety and reduce the consequences of tram and cars accidents. The research to increase the safety of trams, which is carried out at the Czech Technical University in Prague, aims to increase the active and passive safety of trams. Components and systems of active safety are design to reduce the risk of an accident. Components and systems of passive safety are design to minimize the consequences of accidents. One of the elements of passive safety is the partner protection (vehicle compatibility in the accident), which means an approach where the effort is to protect passengers inside and outside the vehicle. The article describes the conclusions from the partial research work on increasing the partner protection of trams in the event of an accident with cars.